Effects of scaffolded intensive reading on students’ reading comprehension performance - Sevilla Morales, Henry (Universidad de Costa Rica, 2017)
Abstract: This research sought to explore the connection between a small-group intensive reading comprehension project and students’ performance in two sample English national exit exams (ENEEs) developed by the Ministry of Public Education, Costa Rica. The data were gathered from an intervention plan that combined the theoretical principles of schema theory, scaffolded reading comprehension, and intensive reading. The study adopts an action-research approach and uses a mixed design that combines quantitative and qualitative data in the analysis and interpretation of results. Participants included twelve students from a public high school in the Western Area of Costa Rica who needed special preparation for the ENEE, which narrows the research scope down to this population only. The data collection techniques included two sample ENEEs, field notes, and research artifacts. Findings reveal positive effects of scaffolded reading comprehension on student ENEE performance, but also they warn that generalizations to larger populations are not possible. The study yields implications at theoretical and practical levels, and it calls for further investigation as a way to tackle the limitations identified.